Urban forestry and ethno medicine: The meeting point in malaria control in Ijesa Region, Nigeria - Alice Temitope Cole; Joshua Kayode (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Malaria-curing trees species were identified among the urban tree species previously identified in Ijesa Region of Nigeria. 25 communities were randomly selected from the region and used for this study. In each community, four adults who have lived in the community continuously for at least 10 years were purposively selected and interviewed on the medicinal values of the urban trees in the region through the use of a semi-structured questionnaire matrix. The ethnomedicinal recipes of the identified malaria-curing tree species were documented. Results obtained revealed that respondents were conscious of the medicinal values of the urban trees. 11 out of the 34 indentified tree species were used for malaria control. The malaria-curing trees were 344 out of 2156 urban trees sampled in the region. This was considered low in view of their medicinal value thus stressed the need to encourage urban tree cultivation among the populace. The malaria plant-based medicine was prepared using simple technology that mostly involved boiling in water. Thus their preparations are attainable by everybody. The extractions of most of the identified species were mostly non-annihilative but extractions predatory and annihilative extractions occurred in four species. Sustainable strategies to improve on urban tree cultivation were proposed.